Combination immunotherapy and radiotherapy causes an abscopal treatment response in a mouse model of castration resistant prostate cancer. Issue 1 (14th August 2019) - Dudzinski, Stephanie O.; Cameron, Brent D.; Wang, Jian; Rathmell, Jeffrey C.; Giorgio, Todd D.; Kirschner, Austin N.
Abstract : Background: Prostate cancer is poorly responsive to immune checkpoint inhibition, yet a combination with radiotherapy may enhance the immune response. In this study, we combined radiotherapy with immune checkpoint inhibition (iRT) in a castration-resistant prostate cancer (CRPC) preclinical model. Methods: Two Myc-CaP tumor grafts were established in each castrated FVB mouse. Anti-PD-1 or anti-PD-L1 antibodies were given and one graft was irradiated 20 Gy in 2 fractions. Results: In CRPC, a significant increase in survival was found for radiation treatment combined with either anti-PD-1 or anti-PD-L1 compared to monotherapy. The median survival for anti-PD-L1 alone was 13 days compared to 30 days for iRT ( p  = 0.0003), and for anti-PD-1 alone was 21 days compared to 36 days for iRT ( p  = 0.0009). Additional treatment with anti-CD8 antibody blocked the survival effect. An abscopal treatment effect was observed for iRT in which the unirradiated graft responded similarly to the irradiated graft in the same mouse. At 21 days, the mean graft volume for anti-PD-1 alone was 2094 mm 3 compared to iRT irradiated grafts 726 mm 3 ( p  = 0.04) and unirradiated grafts 343 mm 3 ( p  = 0.0066). At 17 days, the mean graft volume for anti-PD-L1 alone was 1754 mm 3 compared to iRT irradiated grafts 284 mm 3 ( p  = 0.04) and unirradiated grafts 556 mm 3 ( p  = 0.21). Flow cytometry and immunohistochemistry identified CD8+ immune cell populations altered by combination treatment in grafts harvested at the peak effect of immunotherapy, 2–3 weeks after starting treatment. Conclusions: These data provide preclinical evidence for the use of iRT targeting PD-1 and PD-L1 in the treatment of CRPC. Immune checkpoint inhibition combined with radiotherapy treats CPRC with significant increases in median survival compared to drug alone: 70% longer for anti-PD-1 and 130% for anti-PD-L1, and with an abscopal treatment effect. Precis: Castration-resistant prostate cancer in a wild-type mouse model is successfully treated by X-ray radiotherapy combined with PD-1 or PD-L1 immune checkpoint inhibition, demonstrating significantly increased median overall survival and robust local and abscopal treatment responses, in part mediated by CD8 T-cells.